Autonomous AI Agents in Online Retail: The Next Leap in Programmatic Media Buying - Ameya Gokhale, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The retail industry stands at the brink of transformation driven by autonomous AI agents that will redefine shopping experiences, optimize advertising strategies, and streamline seller onboarding. AI agents will be personalized shopping assistants, intelligent advertising optimizers, and automated seller support systems, creating a seamless and highly efficient retail ecosystem. This technological evolution will personalize consumer interactions, automate advertising campaign management, and lower entry barriers for sellers, making e-commerce more accessible and profitable for all stakeholders. The article examines how AI agents will revolutionize multiple facets of retail, from AI-enhanced augmented reality shopping and group buying experiences to dynamic ad targeting and autonomous ad buying with reinforcement learning, ultimately delivering unprecedented value across the retail value chain through increased efficiency, personalization, and accessibility.
Keywords: Autonomous AI agents; Personalized shopping; Programmatic advertising; Seller ecosystems; Omnichannel retail